Physiological and pharmacological impact of oxytocin on epididymal propulsion during the ejaculatory process in rodents and men. Issue 6 (27th May 2021) - Stadler, Beatrix; Nowell, Cameron J.; Whittaker, Michael R.; Arnhold, Stefan; Pilatz, Adrian; Wagenlehner, Florian M.; Exintaris, Betty; Middendorff, Ralf
Abstract: During the emission phase of ejaculation, the sperm is driven from the cauda epididymidis, where it is stored, through the vas deferens by strong contractions. These contractions are thought of as being mainly induced by the sympathetic nervous system and the neurotransmitter noradrenaline. In the present study, we investigated the effect of oxytocin (suggested to exert effects during ejaculation as well) on defined segments of the rat and human epididymis using live imaging. Our results indicate that it is the very last part of the epididymis, segment 19 (S19) in rat and likewise segment 9 in human, which responds in a uniquely strong and rapid manner to oxytocin (similar to noradrenaline). Because of the complex nature of this contractile response, we developed an imaging analysis method, which allowed us to quantify multidirectional contractions and to display them using heat maps. The reaction of S19 to oxytocin was concentration‐dependent and could be inhibited by pretreatment with oxytocin antagonists (atosiban and cligosiban), but not with an arginine vasopressin 1A antagonist (SR49059). In both rat and human tissue, pretreatment with the alpha‐1 adrenoreceptor antagonist tamsulosin inhibited the response to noradrenaline, whereas the effect of oxytocin was unimpaired. Our data (from men and rodents) strongly suggest that the hormone oxytocin is involved in the ejaculatory process. Thus, oxytocin‐based medications might be a promising non‐adrenergic treatment option for ejaculatory disorders. Additionally, we propose that S19 could be an advantageous model (detecting very low concentrations of oxytocin) to test the bioactivity of new oxytocin agonists and oxytocin antagonists.